Evaluasi Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada PT. Alfa Global Indonesia - Rostiaty Yunus (STIM LASHARAN JAYA MAKASSAR, 2021)
This research aimed to find out the implementation of system of cash flow accountancy at PT. Alfa Global Indonesia. The design of this research was done to analyze the system of cash flow accountancy at PT. Alfa Global Indonesia. The method used was descriptive qualitative to describe the theory of accountancy cash flow system at PT. Alfa Global Indonesia. The result of this research indicated cash flow accountancy system at PT. Alfa Global Indonesia was done well. The system used was more accurate and the information released was very supporting to make decision.